2005
DOI: 10.1080/09513590400027281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy on plasma viscosity and Doppler variations in postmenopausal non-smokers and heavy smokers

Abstract: Cigarette smoking represents a cardiovascular risk factor that can only partially be modified by the administration of transdermal HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…No association between HRT type and Doppler values were found. Previous studies evaluated the effects of HRT on blood vessels and cardiovascular risk factors in HRT receiving postmenopausal women [15][16][17]. Some authors have also described that receiving HRT reduces morbidity and mortality from coronary artery disease [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…No association between HRT type and Doppler values were found. Previous studies evaluated the effects of HRT on blood vessels and cardiovascular risk factors in HRT receiving postmenopausal women [15][16][17]. Some authors have also described that receiving HRT reduces morbidity and mortality from coronary artery disease [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that, like the internal carotid artery PI, the ophthalmic artery PI was significantly higher in the heavy smokers and resulted positively correlated with cigarette use (r = 0.343; P < 0.0001). We speculated that the increased arterial stiffness (due to reduced prostacyclin production, increased thromboxane circulating levels, and increased platelet aggregation) [6], worsening the cerebral vascularization, may increase the risk of cerebrovascular disease in young, healthy smokers. In addition, altered Doppler flow parameters behave as a marker for patients with preclinical vascular disease and may identify, at an early age, women in whom therapeutic intervention (i.e., quitting smoking, body weight control, and decreased salt intake) could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thoracic aortic atherosclerotic lesions as assessed by transesophageal echocardiography resulted increased in smokers vs. nonsmokers [4]. In addition, it has also been reported that cigarette smoking is associated with a significant increase of carotid intima‐media thickness and carotid stiffness as assessed by carotid ultrasound and Doppler analyses [5,6].…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies suggest that oestrogen can be associated with more favourable eicosanoid profiles. In post-menopausal females, plasma thromboxane B 2 and vascular impedance, measured by carotid Doppler, were reduced after starting hormone replacement therapy[36]. Another study found an increased urinary PGI-M-to- 11dTxB 2 ratio with hormone replacement therapy[37].…”
Section: Discussionmentioning
confidence: 99%